2015
DOI: 10.1242/jcs.173211
|View full text |Cite
|
Sign up to set email alerts
|

The yeast Pmp3p has a significant role in plasma membrane organization

Abstract: Pmp3p-related proteins are highly conserved proteins that exist in bacteria, yeast, nematodes and plants, and its transcript is regulated in response to abiotic stresses, such as low temperature or high salinity. Pmp3p was originally identified in Saccharomyces cerevisiae, and it belongs to the sensitive to Na + (SNA)-protein family, which comprises four members -Pmp3p/Sna1p, Sna2p, Sna3p and Sna4p. Deletion of the PMP3 gene conferred sensitivity to cytotoxic cations, whereas removal of the other SNA genes did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Yeast crude membrane extracts were prepared as previously described (22), except that no dithiothreitol was added. Yeast total cell extracts were prepared as previously described (23), except that cells were resuspended in 200 l of cold homogenization medium (250 mM sorbitol, 50 mM imidazole, 1 mM MgCl 2 , pH 7.5) containing a protease inhibitor mix (1 mM PMSF and 2 g/ml each of leupeptin, aprotinin, antipain, pepstatin, and chymostatin) before breaking. The protein concentration was then determined using Bicinchoninic assay, as previously described (24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast crude membrane extracts were prepared as previously described (22), except that no dithiothreitol was added. Yeast total cell extracts were prepared as previously described (23), except that cells were resuspended in 200 l of cold homogenization medium (250 mM sorbitol, 50 mM imidazole, 1 mM MgCl 2 , pH 7.5) containing a protease inhibitor mix (1 mM PMSF and 2 g/ml each of leupeptin, aprotinin, antipain, pepstatin, and chymostatin) before breaking. The protein concentration was then determined using Bicinchoninic assay, as previously described (24).…”
Section: Methodsmentioning
confidence: 99%
“…q-RT-PCR-Total RNA was extracted and analyzed by quantitative real-time PCR as previously described (23). Oligonucleotides designed for real-time PCR are listed in supplemental Table S4.…”
Section: T ϭ Average Of Log Ratios Standard Errormentioning
confidence: 99%
“…For both Hsp90 and Hsp70, there is evidence of the ability to interact preferentially with lipid raft domains (69,70). It has also been reported that the sphingolipid-binding protein Pmp3, which is highly conserved in fungi, is a potent AmB resistance factor (71,72). Such resistance can be suppressed by the addition of phytosphingosine, a sphingolipid pathway intermediate (73).…”
Section: Amb Resistance In Pathogens Containing Normal Sterol Levelsmentioning
confidence: 99%
“…Pmp3 encode for highly hydrophobic proteins that are embedded in plasma membrane with two putative transmembrane domains and small extracellular and cytoplasmic regions. Pmp3 protein is known to modulate plasma membrane potential to maintain cellular ion homeostasis and helps in survival during salt stress (De Block et al, 2015;Serrano and Rodriguez-Navarro, 2001). It is also suggested that Pmp3 regulates a depolarizing cation and proton leak, reducing sensitivity to salinity and low pH conditions.…”
Section: Introductionmentioning
confidence: 99%